2006
DOI: 10.1207/s15327590ijhc2103_3
|View full text |Cite
|
Sign up to set email alerts
|

"You've Got E-Mail!" ... Shall I Deal With It Now? Electronic Mail From the Recipient's Perspective

Abstract: This article considers the nature of e-mail from the recipient's perspective-what the seemingly free and easy communication really costs the recipient. Information gathered by electronic monitoring software is shown to be at odds with the results of an online survey of e-mail users' perceptions of their e-mail experience-users drastically underestimate the disruptive effects of e-mail. The conclusion is that the constant monitoring of e-mail actually reduces productivity and that there is a need for increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 28 publications
2
82
0
3
Order By: Relevance
“…The format of forwarded email threads leads to longer reading times, and the decreased SAT measure indicates that comprehension tasks are more difficult when information appears as a forwarded email thread. Therefore, I contribute to the list of isolated antecedents such as the number of emails (e.g., Dabbish & Kraut, 2006), time spent (e.g., Sumecki et al, 2011), and email-based interruptions (e.g., Gupta et al, 2013;Renaud et al, 2006), which researchers have also investigated as isolated antecedents. Furthermore, these factors are congruent with the findings from an information-overload perspective in terms of the antecedents amount of information (Hiltz & Turoff, 1985;Nelson, 1994) and available time (Schick et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The format of forwarded email threads leads to longer reading times, and the decreased SAT measure indicates that comprehension tasks are more difficult when information appears as a forwarded email thread. Therefore, I contribute to the list of isolated antecedents such as the number of emails (e.g., Dabbish & Kraut, 2006), time spent (e.g., Sumecki et al, 2011), and email-based interruptions (e.g., Gupta et al, 2013;Renaud et al, 2006), which researchers have also investigated as isolated antecedents. Furthermore, these factors are congruent with the findings from an information-overload perspective in terms of the antecedents amount of information (Hiltz & Turoff, 1985;Nelson, 1994) and available time (Schick et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This stream of research has also identified several aspects that causes strain in humans other than the initial focus on the high number of emails (Dabbish & Kraut, 2006). For instance, studies have examined how often emails interrupt people, how much time they spend reading emails, and the optimal timing decision for checking for new emails (Gupta et al, 2013;Gupta et al, 2011;Renaud et al, 2006;Vidgen et al, 2011). Other research focuses on the perception of email as a business-critical tool (Sumecki et al, 2011) or how their personality may influence their sensitivity to email overload (Reinke & Chamorro-Premuzic, 2014).…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It is composed out of a number of unique characteristics such as being asynchronous [20], textual [21], shared [56], traceable [13,57], instantaneous [58] and effcient [22]. Email popularization brought about a large disadvantage: email overload.…”
Section: Knowledge Workers and Handling Emailsmentioning
confidence: 99%
“…The main differences between these two channels pertain to their richness, which relates to the variety of signals that are possible to be shared between communicators [8,11,19]. Both channels further differ in the temporal dimension, namely the synchronous or not nature of the channel, which affects pacing of communication according to the needs and desires of both communicators [20][21][22]. Finally, both channels offer different levels of control the initiator and the recipient have over the communicative occurrence, which is substantiated in the possibility for them to choose when and how to react to communication initiation [14,23].…”
mentioning
confidence: 99%